Bright sub-20-nm cathodoluminescent nanoprobes for electron microscopy. - Prigozhin, Maxim B. (Nat Nanotechnol, 2019)
Electron microscopy (EM) has been instrumental in our understanding of complex biological systems. Although EM reveals cellular morphology with nanoscale resolution, it does not provide information on the location of different types of proteins. An EM-based bioimaging technology capable of localizing individual proteins and resolving protein-protein interactions with respect to cellular ultrastructure would provide important insights into the molecular biology of a cell. Here, we synthesized small lanthanide-doped nanoparticles, and measured the absolute photon emission rate of individual nanoparticles resulting from a given electron excitation flux (cathodoluminescence). Our results suggest that the optimization of nanoparticle composition, synthesis protocols and electron imaging conditions can lead to sub-20-nm nano-labels that would enable high signal-to-noise localization of individual biomolecules within a cellular context. In ensemble measurements, these labels exhibit narrow spectra of nine distinct colors, so that the imaging of biomolecules in a multicolor EM modality may be possible.